An Analysis of the Socio-cultural Implications of Orality in Iran. Issue 2 (June 2023) - Yeganeh, Kia Hamid
This article relies on a leading line of anthropological research on the socio-cultural implications of orality in Iran. The analyses reveal that the prevalence of oral language in Iran is associated with a wide range of implications, such as redundancy, emotionality, ambiguity, high-context culture traits, the lack of critical thinking, the gap between speech and writing, the importance of poetry, restricted scientific and technical knowledge, religiosity, traditionalism, the centrality of negotiating, old-fashioned entrepreneurship, and authoritarian governance and leadership. The article examines the practical consequences of orality on Iranian culture, social relations, and politics.